2012
DOI: 10.1302/0301-620x.94b2.27296
|View full text |Cite
|
Sign up to set email alerts
|

The use of femoral struts and impacted cancellous bone allograft in patients with severe femoral bone loss who undergo revision total hip replacement

Abstract: We determined the midterm survival, incidence of peri-prosthetic fracture and the enhancement of the width of the femur when combining struts and impacted bone allografts in 24 patients (25 hips) with severe femoral bone loss who underwent revision hip surgery. The pre-operative diagnosis was aseptic loosening in 16 hips, second-stage reconstruction in seven, peri-prosthetic fracture in one and stem fracture in one hip. A total of 14 hips presented with an Endoklinik grade 4 defect and 11 hips a grade 3 defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…When comparing femoral width between preoperative measurements and those obtained immediately postoperative and at the latest follow-up, mean increases of 10.5 mm and 7.8 mm, respectively, were observed. These results are in agreement with previously reported data [20,33]. Poor femoral bone stock in revision THA has been shown to influence functional outcomes, [2] increase the risk of aseptic loosening, [5] and increase the risk of periprosthetic fracture [3] and also presents particular problems if further revision is required [4]; the restoration of bone stock is therefore of vital importance in eliminating the correlation between preoperative bone defects and poor clinical outcomes [12].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…When comparing femoral width between preoperative measurements and those obtained immediately postoperative and at the latest follow-up, mean increases of 10.5 mm and 7.8 mm, respectively, were observed. These results are in agreement with previously reported data [20,33]. Poor femoral bone stock in revision THA has been shown to influence functional outcomes, [2] increase the risk of aseptic loosening, [5] and increase the risk of periprosthetic fracture [3] and also presents particular problems if further revision is required [4]; the restoration of bone stock is therefore of vital importance in eliminating the correlation between preoperative bone defects and poor clinical outcomes [12].…”
Section: Discussionsupporting
confidence: 91%
“…Resorption of strut allografts was graded as follows according to Maury et al: mild when the partial-thickness resorption of one cortex was less than 1 cm in length, moderate when the partial-thickness resorption of one cortex was more than 1 cm in length, and severe when full-thickness resorption of the cortex was observed [19]. Femoral width was measured at the zone with the most severe bone loss observed on anteroposterior radiographs, where the strut allografts were always applied to augment the bone stock [20]. To minimize potential errors in the measurement of femoral width caused by femoral rotation, all preoperative and postoperative radiographs were taken using a standard protocol.…”
Section: Radiographic Assessmentmentioning
confidence: 99%
“…Incorporation and remodeling of these allografts to the host bone has been shown to be successful in 80% to 100 % of cases. 51 Buttaro and colleagues, 52 in their cohort of 25 hips (14 with type IV and 11 with type IIIB defects), showed that mean femoral width was increased by 41% and overall survivorship was 95% at a mean of 54.5 months. There was no evidence of osteolysis, resorption, or radiolucencies during follow-up in any hip.…”
Section: Type IV Defectsmentioning
confidence: 99%
“…Severe bone loss is also a major problem in revision joint replacement. Buttaro et al [25] investigated a combination of struts and impacted bone allografts to treat patients with loosening of the hip arthroplasty. Those authors found satisfying survival rates of hip revision and a low incidence of periprosthetic fractures using that method [25].…”
Section: Discussionmentioning
confidence: 99%